Treatment of Locoregional Recurrences of Skin Melanoma (a Clinical Case) - O. N. Ganusevich; T. N. Nesterovich; I. V. Fedorkevich; A. S. Yakovenko (Кубанский научный медицинский вестник, 2020)
Aim. To demonstrate an interesting clinical case of treating a patient with intradermal melanoma metastases.Materials and methods. A patient with intradermal melanoma metastases was given a combined treatment including photodynamic therapy (PDT) and immunotherapy (intradermal administration of an immunological preparation into metastatic foci).Results. A clinical case of a patient with a locoregional recurrence of skin melanoma (SM) of the left lower leg was described. Given the prevalence of the pathological substrate and the presence of concomitant pathologies, two treatment methods were selected – PDT and intradermal administration of interferon into metastatic foci. These methods provided both the local and systemic effect. As a result, the stabilisation of the tumour process was achieved.Conclusion. Combined treatment of locoregional recurrences of skin melanoma using PDT and intrametastatic injections of immunopreparations can be used as an alternative to surgical intervention in somatically weakened patients with a large area of intradermal metastases, which will allow the tumour process to be stabilised. In cases where the area of locoregional intradermal recurrences in somatically compensated patients does not permit surgical treatment, the proposed technique may be the only possible treatment method.